Revisiting the issues of co-branding / Nur Syuhaada Kharil Anuar ... [et al.] - Kharil Anuar, Nur Syuhaada; Zainal Abidin, Izhar Hafifi; Samsudin, Azlina; Adzmy, Azahar; Zulkornain, Luqmanul Hakim (Universiti Teknologi MARA, Perlis, 2021)
In the maturing Malaysian market environment, co-branding is becoming a more common type of growth strategy. Despite being a scheme that could drive companies dedicated to it, some problems emerged tainting the scheme's original goals. Via searches in online databases such as ScienceDirect, Scopus, SpringerLink, and ProQuest ABI/ INFORM Collection, this paper identified related studies published between 1994 and 2019. This search strategy yielded 22 works of literature that meet the conclusion requirements. Four patterns of co-branding issues in the hospitality industry which are management, marketing, product and service, and customer were found using content analysis.